Occurrence of maxillary sinus abnormalities detected by cone beam CT in asymptomatic patients - Rege Inara Carneiro; Sousa Thiago; Leles Cláudio; Mendonça Elismauro (BMC, 2012)
Abstract Background Although cone beam computed tomography (CBCT) images of the maxillofacial region allow the inspection of the entire volume of the maxillary sinus (MS), identifying anatomic variations and abnormalities in the image volume, this is frequently neglected by oral radiologists when interpreting images of areas at a distance from the dentoalveolar region, such as the full anatomical aspect of the MS. The aim of this study was to investigate maxillary sinus abnormalities in asymptomatic patients by using CBCT. Methods 1113 CBCT were evaluated by two examiners and identification of abnormalities, the presence of periapical lesions and proximity to the lower sinus wall were recorded. Data were analyzed using descriptive statistics, chi-square tests and Kappa statistics. Results Abnormalities were diagnosed in 68.2% of cases (kappa = 0.83). There was a significant difference between genders (p < 0.001) and there was no difference in age groups. Mucosal thickening was the most prevalent abnormality (66%), followed by retention cysts (10.1%) and opacification (7.8%). No association was observed between the proximity of periapical lesions and the presence and type of inflammatory abnormalities (p = 0.124). Conclusions Abnormalities in maxillary sinus emphasizes how important it is for the dentomaxillofacial radiologist to undertake an interpretation of the whole volume of CBCT images.